The Analysis of Factors of the Vice President Secretariat Organization's Performance in Supporting the Vice President - Effi Ratna Furkon; Eko Prasojo (Jurnal Administrasi Publik (Public Administration Journal), 2021)
The implementation of the Vice President's broad and dynamic duties must of course be supported by good performance tools. As the Vice President's first support system, the position of the Vice President's Secretariat (Setwapres) was very strategic to improve organizational performance. The purpose of the study was to analyze the performance factors of the Vice President Secretariat in providing support to the Vice President from the perspective of the McKinsey 7S Framework. This research was a descriptive research with a qualitative approach. The study used primary data and secondary data. Primary data sources using the interview method. Secondary data sources using relevant document data search. All data were presented descriptively and analyzed through data reduction, data presentation, and verification. The results of the study indicated that the supporting factors were (1) a structure where there was a clear division of tasks and functions as well as good coordination; (2) a style in which democratic leadership made communication work well with direct involvement of the leadership in carrying out tasks; (3) the existence of shared values accompanied by internalization and strengthening activities. The inhibiting factors were: (1) a strategy in which several activity programs were not in accordance with the Vice President's priority program; (2) a system where the implementation of SOPs was not entirely appropriate; (3) staff where the placement was not in accordance with the educational background; (4) skills that had not been supported by appropriate training.